A progressive and complex clinical course in two family members with ERF-related craniosynostosis: a case report - Izabella Körberg; Daniel Nowinski; Marie-Louise Bondeson; Malin Melin; Lars Kölby; Eva-Lena Stattin (BMC, 2020)
Abstract Background ERF-related craniosynostosis are a rare, complex, premature trisutural fusion associated with a broad spectrum of clinical features and heterogeneous aetiology. Here we describe two cases with the same pathogenic variant and a detailed description of their clinical course. Case presentation Two subjects; a boy with a BLSS requiring repeated skull expansions and his mother who had been operated once for sagittal synostosis. Both developed intracranial hypertension at some point during the course, which was for both verified by formal invasive intracranial pressure monitoring. Exome sequencing revealed a pathogenic truncating frame shift variant in the ERF gene. Conclusions Here we describe a boy and his mother with different craniosynostosis patterns, but both with verified intracranial hypertension and heterozygosity for a truncating variant of ERF c.1201_1202delAA (p.Lys401Glufs*10). Our work provides supplementary evidence in support of previous phenotypic descriptions of ERF-related craniosynostosis, particularly late presentation, an evolving synostotic pattern and variable expressivity even among affected family members.